Factors of Talent Retention in Malaysian Construction Industry: Employee’s Perspective - Li Yee, Kwan; Mansor, Nur Syaimasyaza (Online Journal for TVET Practitioners, 2023)
Engaging and retaining high-quality employees is critical to achieving an organization’s objectives. Employee turnover can cause a shortage of skilled manpower, ultimately leading to reduced innovation, lower labour productivity, etc. In the construction industry, employee turnover will cause project delays, project quality defects, client dissatisfaction, and profitability challenges. As the construction industry is critical to Malaysia’s development, organizations must ensure smooth operations by retaining their talents. This paper reports on the significant factors of talent retention in the Malaysian construction industry. The methodology adopted was literature review and quantitative method via a questionnaire survey. 12 predefined factors identified from literature review were presented to the respondents in the questionnaire. The target respondents for this study were construction professionals from G7 contractor, and a total of 77 responses were obtained. The significance of the factors was assessed and ranked using their average mean scores. The top five factors influencing talent retention are: 1) management and social support; 2) compensation and benefits; 3) work environment; 4) organizational commitment (employee loyalty); 5) nature of work (meaningfulness). This study would serve as a reference for employers to take necessary proactive action to retain employees and ensure the efficiency and survival of the industry.